Venous tone and cardiac function in the South American rattlesnake Crotalus durissus: mean circulatory filling pressure during adrenergic stimulation in anaesthetised and fully recovered animals - Skals, M.; Skovgaard, N.; Abe, Augusto Shinya; Wang, T. (Company of Biologists Ltd, 2005)
The effects of adrenergic stimulation on mean circulatory filling pressure (MCFP), central venous pressure (P-CV) and stroke volume (Vs), as well as the effects of altered MCFP through changes of blood volume were investigated in rattlesnakes (Crotalus durissus). MCFP is an estimate of the upstream pressure driving blood towards the heart and is determined by blood volume and the activity of the smooth muscle cells in the veins (venous tone). MCFP can be determined as the plateau in P-CV during a total occlusion of blood flow from the heart.Vs decreased significantly when MCFP was lowered by reducing blood volume in anaesthetised snakes, whereas increased MCFP through infusion of blood (up to 3 ml kg(-1)) only led to a small rise in Vs. Thus, it seems that end-diastolic volume is not affected by an elevated MCFP in rattlesnakes. To investigate adrenergic regulation on venous tone, adrenaline as well as phenylephrine and isoproterenol (alpha- and beta-adrenergic agonists, respectively) were infused as bolus injections (2 and 10 mu g kg(-1)). Adrenaline and phenylephrine caused large increases in MCFP and P-CV, whereas isoproterenol decreased both parameters. This was also the case in fully recovered snakes. Therefore, adrenaline affects venous tone through both alpha- and beta-adrenergic receptors, but the alpha-adrenergic receptor dominates at the dosages used in the present study. Injection of the nitric oxide donor SNP caused a significant decrease in P-CV and MCFP. Thus, nitric oxide seems to affect venous tone.
Keywords: reptile; Crotalus durissus; cardiovasular control; adrenergic regulation; venous tone; mean circulatory filling pressure; venous return